2015
DOI: 10.1371/journal.pone.0131339
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium simium, a Plasmodium vivax-Related Malaria Parasite: Genetic Variability of Duffy Binding Protein II and the Duffy Antigen/Receptor for Chemokines

Abstract: Plasmodium simium is a parasite from New World monkeys that is most closely related to the human malaria parasite Plasmodium vivax; it also naturally infects humans. The blood-stage infection of P. vivax depends on Duffy binding protein II (PvDBPII) and its cognate receptor on erythrocytes, the Duffy antigen receptor for chemokines (hDARC), but there is no information on the P. simium erythrocytic invasion pathway. The genes encoding P. simium DBP (PsDBPII) and simian DARC (sDARC) were sequenced from Southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…The results of the present study, uncovering a haplotype diversity in a situation of low genetic divergence in Espírito Santo, indicate a heterogeneity of the isolates obtained from different host species, and strengthen the understanding that P. vivax and P. simium are the same species with small genetic variations. What is more, these results corroborate the findings of Costa et al [ 35 ] and Rodrigues et al [ 25 ], whose phylogenetic analyses of samples from different world regions indicated a recent transfer of the parasite from humans to New World simians.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study, uncovering a haplotype diversity in a situation of low genetic divergence in Espírito Santo, indicate a heterogeneity of the isolates obtained from different host species, and strengthen the understanding that P. vivax and P. simium are the same species with small genetic variations. What is more, these results corroborate the findings of Costa et al [ 35 ] and Rodrigues et al [ 25 ], whose phylogenetic analyses of samples from different world regions indicated a recent transfer of the parasite from humans to New World simians.…”
Section: Discussionsupporting
confidence: 91%
“…Second, though rare, ape-to-human P. vivax transmission has been reported in Central Africa [8]. Finally, P. vivax has been secondarily transmitted from humans to New World monkeys multiple times, yielding a post-Columbian host shift (deemed P. simium ) less than 500 years ago [12,53,54]. These observations suggest that further research into the host promiscuity of P. vivax is warranted.…”
Section: Plasmodium Vivax: a Long Neglected Pandemicmentioning
confidence: 99%
“…A few Brazilian studies in the literature have demonstrated successful sequencing, generally through using fragments generated from the genes that code the circumsporozoite protein (CSP) or merozoite surface protein (MSP) [ 45 , 60 ]. More recently, other targets have also been used for sequencing malaria parasites from NTPs, such as using Duffy binding protein [ 61 ] and 18S rRNA [ 20 ]. However, more commonly, studies have not included sequencing, even when analyzing large numbers of samples [ 19 , 62 ].…”
Section: Discussionmentioning
confidence: 99%